Solid polymer electrolyte for lithium battery
By adding ceramic electrolyte nanoparticles and lithium ion-filled porous activated carbon powder to the solid polymer electrolyte of lithium batteries, the problems of low conductivity and insufficient stability are solved, and the transmission efficiency of lithium ions and the stability of electrolyte are significantly improved.
Patent Information
- Application Number
- CN202411554362.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The solid polymer electrolytes of existing lithium batteries have low conductivity, insufficient thermal stability and electrochemical stability, and dendrite growth problems, which limit their application in lithium batteries.
By preparing ceramic electrolyte nanoparticles and lithium ion filled porous activated carbon powder, mixed and dispersing them evenly in polyethylene oxide, a solid polymer electrolyte for lithium batteries is formed.
It significantly improves the lithium ion transmission efficiency of solid polymer electrolytes, improves its ionic conductivity, improves thermal stability and electrochemical stability, and solves dendrites' growth problem.
Smart Images

Figure BDA0005116008160000091 
Figure BDA0005116008160000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a solid polymer electrolyte for lithium batteries. Background Art
[0002] Lithium-ion battery electrolytes are mainly divided into two types: electrolytes and polymer electrolytes. The electrolyte is mainly composed of high-purity organic solvents, lithium salts, and certain functional additives with modifying effects. Positive and negative ions can dissolve in the electrolyte and migrate quickly, making the electrolyte have good conductivity. Therefore, commercial lithium batteries currently mainly use electrolytes. However, there are also some problems with the electrolyte itself, such as: the electrolyte limits the shape of the lithium battery, making it impossible to make a flexible battery, which limits the application range of lithium-ion batteries; the electrolyte is expensive and easy to leak, and it will explode under collision and high temperature, posing serious safety hazards. In order to solve these problems with the electrolyte, scientists began to focus on the research of safer and more superior polymer electrolytes to replace traditional electrolytes and prepare practical polymer lithium-ion batteries.
[0003] Solid polymer electrolyte is a material that has been widely studied and used in lithium-ion batteries (Li-ion) and other high-energy-density batteries. Compared with traditional liquid electrolytes, solid polymer electrolytes have many advantages, such as higher safety, greater battery energy density, wider operating temperature range, etc.
[0004] The main components of polymer solid electrolytes include polymer matrix and alkali metal salts. Polymer electrolytes originated from the polyethylene oxide (PEO)-alkali metal salt complex reported by Wright et al. in 1973. Subsequently, ionically conductive polymers have received widespread attention. In 1979, Amand et al. first reported a PEO-based lithium-ion polymer electrolyte and successfully prepared a polymer battery. Since then, polymer solid electrolytes have made significant progress in both theoretical research and practical applications, and different types of polymer electrolytes have gradually been developed.
[0005] Polymer solid electrolytes can avoid the risk of leakage and electric leakage of liquid electrolytes, and are relatively stable to metallic lithium. At the same time, polymer solid electrolytes are flexible and easy to process, and can be prepared into various shapes and films according to different needs. Polymer solid electrolytes have good plasticity and can maintain full contact with the electrodes, reducing the electrolyte / electrode interface resistance. However, there are still many problems with polymer solid electrolytes. For example: polymer solid electrolytes have low electrical conductivity, and their thermal stability and electrochemical stability are poorer than those of inorganic solid electrolytes. In addition, the problem of dendrite growth cannot be completely solved in polymer solid electrolytes.
[0006] The main research directions and improvement methods of solid polymer electrolytes for lithium batteries at present:
[0007] Improving ionic conductivity: Increasing the ionic conductivity of solid electrolytes is a major research direction. This can be achieved by improving the chemical composition and structure of the electrolyte or adding conductive fillers. For example, exploring new high ionic conductivity materials and optimizing the lithium salt concentration of polymer electrolytes can improve ionic conductivity.
[0008] Improving mechanical stability: Solid electrolytes need to have sufficient mechanical stability to cope with battery charge and discharge cycles and temperature changes. Researchers are committed to improving the mechanical properties of electrolytes in material design to reduce cracking and damage of solid electrolytes.
[0009] Reduce the interfacial resistance of the electrolyte: The resistance between the solid electrolyte and the electrode material is an important limiting factor in battery performance. Improving the interface between the electrolyte and the electrode and reducing the interfacial resistance can improve the power performance and charge and discharge efficiency of the battery.
[0010] Improving the operating temperature range: Solid-state electrolytes usually perform better at lower temperatures, but their performance decreases at higher temperatures. Researchers are working to expand the operating temperature range of solid-state electrolytes to accommodate a variety of application scenarios.
[0011] Reducing manufacturing costs: Achieving low-cost solid-state electrolyte preparation methods is an important research direction. This includes developing cheaper raw materials, simplifying the manufacturing process, and improving production efficiency.
[0012] Safety improvements: Solid-state electrolytes have attracted much attention due to their lower risk of fire and explosion, but safety remains an important research direction. Researchers look for safer electrolyte materials and design automatic power-off mechanisms to deal with abnormal situations.
[0013] Hierarchical electrolytes: Some research teams have applied hierarchical structures to solid electrolytes to achieve better performance. These structures include nanoparticles, porous structures, and composite materials to enhance the conductivity and stability of the electrolytes.
[0014] How to further improve the conductivity and stability of solid electrolytes has become an urgent problem to be solved. Summary of the invention
[0015] In view of the defects in the prior art, the present invention discloses a solid polymer electrolyte for a lithium battery.
[0016] The specific technical solutions of the present invention are as follows:
[0017] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0018] Ceramic electrolyte nanoparticles and porous activated carbon powder filled with lithium ions are prepared, and the ceramic electrolyte nanoparticles and the porous activated carbon powder filled with lithium ions are mixed and uniformly dispersed in polyethylene oxide to obtain the solid polymer electrolyte for lithium batteries.
[0019] Preferably, a method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0020] (1) dissolving lithium nitrate, tetrabutyl titanate, zirconium oxychloride octahydrate and aluminum trichloride hexahydrate in a citric acid-ethylene glycol solution, stirring to form a transparent solution, and drying the solution to obtain a transparent gel; calcining the transparent gel at a high temperature to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0021] (2) washing, drying, shearing, crushing and sieving coconut shell fiber to obtain coconut shell fiber powder; treating the obtained cellulose with sodium hydroxide aqueous solution, filtering, washing and drying to obtain activated cellulose powder;
[0022] (3) immersing the activated cellulose powder obtained in step (2) in a copper chloride aqueous solution, stirring, filtering, and oxidizing to obtain a cellulose powder filled with copper oxide; immersing the cellulose powder filled with copper oxide in sulfuric acid, stirring, filtering, washing, and drying to obtain a porous cellulose powder;
[0023] (4) mixing the porous cellulose powder obtained in step (3), lithium nitrate and water, filtering and drying to obtain a porous cellulose powder filled with lithium ions; calcining the porous cellulose powder filled with lithium ions in an oxygen-free environment to obtain a porous activated carbon powder filled with lithium ions;
[0024] (5) mixing the ceramic electrolyte nanoparticles obtained in step (1) and the porous activated carbon powder filled with lithium ions obtained in step (4) to obtain a mixed electrolyte; dissolving polyethylene oxide in anhydrous acetonitrile, then adding the mixed electrolyte, stirring and repeatedly ultrasonicating to ensure that the mixed electrolyte is fully dispersed, coating the obtained uniform suspension on a polytetrafluoroethylene substrate, and fully drying under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0025] Preferably, a method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0026] (1) dissolving 4-5 parts of lithium nitrate, 1-1.5 parts of tetrabutyl titanate, 1.5-2 parts of zirconium oxychloride octahydrate and 3-4 parts of aluminum trichloride hexahydrate in 10-20 parts of citric acid-ethylene glycol solution by mass, stirring to form a transparent solution, and drying the solution to obtain a transparent gel; calcining the transparent gel at 600-700° C. for 1-2 hours to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0027] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 180-200 mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 6-8 wt % sodium hydroxide aqueous solution for 1-2 h, filtering, washing and drying to obtain activated cellulose powder;
[0028] (3) immersing the activated cellulose powder obtained in step (2) in a copper chloride aqueous solution with a concentration of 18-20 wt% at a bath ratio of 1 g: (10-20) mL, stirring for 1-2 h, filtering, and oxidizing at 100-120° C. for 6-8 h to obtain a cellulose powder filled with copper oxide; immersing the above copper oxide-filled cellulose powder in 10-16 wt% sulfuric acid at a bath ratio of 1 g: (10-20) mL, stirring for 15-30 min, filtering, washing, and drying to obtain a porous cellulose powder;
[0029] (4) Mixing 5-10 parts of the porous cellulose powder obtained in step (3), 1.6-2 parts of lithium nitrate, and 40-50 parts of water, by mass, and stirring for 1-2 hours, filtering, and drying to obtain a porous cellulose powder filled with lithium ions; calcining the porous cellulose powder filled with lithium ions at 600-800° C. in an oxygen-free environment to obtain a porous activated carbon powder filled with lithium ions;
[0030] (5) The ceramic electrolyte nanoparticles obtained in step (1) and the porous activated carbon powder filled with lithium ions obtained in step (4) are mixed in a mass ratio of 1:(0.1-0.2) to obtain a mixed electrolyte; 8-12 parts of polyethylene oxide are dissolved in 90-100 parts of anhydrous acetonitrile by mass, and then 1-1.5 parts of the mixed electrolyte are added, stirred and ultrasonicated for 40-60 minutes, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 50-70° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0031] The ultrasonic power in step (5) is 600-1000W and the frequency is 40-80kHz.
[0032] The porous activated carbon powder filled with lithium ions is added to the solid polymer electrolyte prepared by the present invention, which can greatly improve the lithium ion transmission efficiency of the solid polymer electrolyte, thereby improving the ionic conductivity. The present invention first uses common coconut shell fiber as a carrier, which is cheap and low in cost, and then uses sodium hydroxide to activate it so that it can adsorb more metal ions, then uses copper ion adsorption and oxidation to expand the cellulose structure and produce more active sites, and finally removes copper ions and adsorbs lithium ions to obtain porous fibers filled with lithium ions. However, due to the weak conductivity and strong water absorption of cellulose, it not only affects the transmission efficiency of lithium ions, but also brings certain dangers to the battery. In order to further improve the ionic conductivity of the prepared solid electrolyte, the present invention performs high-temperature carbonization treatment on the porous cellulose powder filled with lithium ions to obtain a porous activated carbon powder containing a large amount of lithium ions, which can effectively form a stable lithium ion transmission channel in the solid polymer electrolyte, greatly improving the electronic transmission efficiency of the prepared solid electrolyte.
[0033] Beneficial effects of the present invention:
[0034] The present invention firstly adopts common coconut shell fiber as a carrier, which is inexpensive and low in cost, then adopts a porous method to enhance the adsorption capacity of coconut shell fiber for lithium ions, and finally carbonizes to obtain porous activated carbon powder filled with lithium ions; the porous activated carbon powder filled with lithium ions is added to the solid polymer electrolyte prepared by the present invention, which can greatly improve the lithium ion transmission efficiency of the solid polymer electrolyte, thereby improving the ion conductivity. DETAILED DESCRIPTION
[0035] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0036] Example 1
[0037] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0038] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0039] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 7 wt % sodium hydroxide aqueous solution for 1 h, filtering, washing and drying to obtain activated cellulose powder;
[0040] (3) immersing the activated cellulose powder obtained in step (2) in a 20 wt % copper chloride aqueous solution at a bath ratio of 1 g: 20 mL, stirring for 1 h, filtering, and oxidizing at 100° C. for 8 h to obtain a cellulose powder filled with copper oxide; immersing the above copper oxide-filled cellulose powder in 12 wt % sulfuric acid at a bath ratio of 1 g: 20 mL, stirring for 20 min, filtering, washing, and drying to obtain a porous cellulose powder;
[0041] (4) Mixing 8 parts of the porous cellulose powder obtained in step (3), 1.8 parts of lithium nitrate and 50 parts of water for 2 hours, filtering and drying to obtain a porous cellulose powder filled with lithium ions; calcining the porous cellulose powder filled with lithium ions at 700° C. in an oxygen-free environment to obtain a porous activated carbon powder filled with lithium ions;
[0042] (5) The ceramic electrolyte nanoparticles obtained in step (1) and the porous activated carbon powder filled with lithium ions obtained in step (4) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0043] The ultrasonic power in step (5) is 800W and the frequency is 60kHz.
[0044] Example 2
[0045] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0046] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0047] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 7 wt % sodium hydroxide aqueous solution for 1 h, filtering, washing and drying to obtain activated cellulose powder;
[0048] (3) Mixing 8 parts of the activated cellulose powder obtained in step (2), 1.8 parts of lithium nitrate and 50 parts of water, by mass, and stirring for 2 hours, filtering and drying to obtain lithium ion-loaded cellulose powder; calcining the lithium ion-loaded cellulose powder at 700° C. in an oxygen-free environment to obtain lithium ion-loaded activated carbon powder;
[0049] (5) The ceramic electrolyte nanoparticles obtained in step (1) and the lithium ion-loaded activated carbon powder obtained in step (4) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the resulting uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0050] The ultrasonic power in step (5) is 800W and the frequency is 60kHz.
[0051] Example 3
[0052] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0053] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0054] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 7 wt % sodium hydroxide aqueous solution for 1 h, filtering, washing and drying to obtain activated cellulose powder;
[0055] (3) immersing the activated cellulose powder obtained in step (2) in a 20 wt % copper chloride aqueous solution at a bath ratio of 1 g: 20 mL, stirring for 1 h, filtering, and oxidizing at 100° C. for 8 h to obtain a cellulose powder filled with copper oxide; immersing the above copper oxide-filled cellulose powder in 12 wt % sulfuric acid at a bath ratio of 1 g: 20 mL, stirring for 20 min, filtering, washing, and drying to obtain a porous cellulose powder;
[0056] (4) Mix 8 parts of the porous cellulose powder obtained in step (3), 1.8 parts of lithium nitrate, and 50 parts of water, and stir for 2 hours, filter, and dry to obtain a porous cellulose powder filled with lithium ions;
[0057] (5) The ceramic electrolyte nanoparticles obtained in step (1) and the lithium ion-filled porous cellulose powder obtained in step (4) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the resulting uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0058] The ultrasonic power in step (5) is 800W and the frequency is 60kHz.
[0059] Comparative Example 1
[0060] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0061] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0062] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; calcining the coconut shell fiber powder at 700° C. in an oxygen-free environment to obtain carbon powder;
[0063] (3) The ceramic electrolyte nanoparticles obtained in step (1) and the carbon powder obtained in step (2) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0064] The ultrasonic power in step (3) is 800W and the frequency is 60kHz.
[0065] Comparative Example 2
[0066] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0067] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0068] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 7 wt % sodium hydroxide aqueous solution for 1 h, filtering, washing and drying to obtain activated cellulose powder;
[0069] (3) calcining the activated cellulose powder obtained in step (2) at 700° C. in an oxygen-free environment to obtain carbon powder;
[0070] (4) The ceramic electrolyte nanoparticles obtained in step (1) and the carbon powder obtained in step (3) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0071] The ultrasonic power in step (4) is 800W and the frequency is 60kHz.
[0072] Comparative Example 3
[0073] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0074] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0075] (2) washing, drying, shearing and crushing coconut shell fiber, passing through a 200-mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 7 wt % sodium hydroxide aqueous solution for 1 h, filtering, washing and drying to obtain activated cellulose powder;
[0076] (3) immersing the activated cellulose powder obtained in step (2) in a 20 wt % copper chloride aqueous solution at a bath ratio of 1 g: 20 mL, stirring for 1 h, filtering, and oxidizing at 100° C. for 8 h to obtain a cellulose powder filled with copper oxide; immersing the above copper oxide-filled cellulose powder in 12 wt % sulfuric acid at a bath ratio of 1 g: 20 mL, stirring for 20 min, filtering, washing, and drying to obtain a porous cellulose powder;
[0077] (4) calcining the porous cellulose powder at 700° C. in an oxygen-free environment to obtain porous activated carbon powder;
[0078] (5) The ceramic electrolyte nanoparticles obtained in step (1) and the porous activated carbon powder obtained in step (4) are mixed in a mass ratio of 1:0.16 to obtain a mixed electrolyte; 10 parts of polyethylene oxide are dissolved in 90 parts of anhydrous acetonitrile by mass, and then 1.2 parts of the mixed electrolyte are added, stirred and ultrasonicated for 50 minutes, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate, and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0079] The ultrasonic power in step (5) is 800W and the frequency is 60kHz.
[0080] Comparative Example 4
[0081] A method for preparing a solid polymer electrolyte for a lithium battery comprises the following steps:
[0082] (1) By weight, 4.13 parts of lithium nitrate, 1.20 parts of tetrabutyl titanate, 1.61 parts of zirconium oxychloride octahydrate and 3.40 parts of aluminum trichloride hexahydrate are dissolved in 16 parts of citric acid-ethylene glycol solution, stirred to form a transparent solution, and the solution is dried to obtain a transparent gel; the transparent gel is calcined at 600° C. for 2 h to remove carbon therein, thereby obtaining ceramic electrolyte nanoparticles;
[0083] (2) By mass, 10 parts of polyethylene oxide were dissolved in 90 parts of anhydrous acetonitrile, and then 1.2 parts of the ceramic electrolyte nanoparticles obtained in step (1) were added, stirred and ultrasonicated for 50 minutes, and the resulting uniform suspension was coated on a polytetrafluoroethylene substrate and dried at 60° C. under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
[0084] The ultrasonic power in step (2) is 800W and the frequency is 60kHz.
[0085] Test Example 1
[0086] The solid polymer electrolyte was placed between stainless steel electrodes, and the ionic conductivity (δ) was then measured by AC impedance measurement in the frequency band from 100 MHz to 0.1 Hz using a VMP3 measuring device and 4294 (δ = l / (R×A), δ is the ionic conductivity (mS / cm), l is the thickness of the electrolyte (cm), R is the measured resistance (mS), and A is the area of the electrolyte (cm 2 ))
[0087] Table 1: Ionic conductivity test results
[0088]
[0089]
[0090] As can be seen from Table 1, the solid polymer electrolyte for lithium batteries prepared in Example 1 of the present invention has the highest conductivity. Compared with Comparative Example 4, its ion conductivity has been significantly improved. The present invention believes that this is because the porous activated carbon powder filled with lithium ions is added to the solid polymer electrolyte prepared in Example 1, which can greatly improve the lithium ion transmission efficiency of the solid polymer electrolyte, thereby improving the ion conductivity. The present invention first uses common coconut shell fiber as a carrier, which is cheap and low in cost, and then uses sodium hydroxide to activate it so that it can adsorb more metal ions. Then, copper ions are adsorbed and oxidized to expand the cellulose structure and produce more active sites. Finally, copper ions are removed and lithium ions are adsorbed to obtain porous fibers filled with lithium ions. However, since cellulose has weak conductivity and strong water absorption, it not only affects the transmission efficiency of lithium ions, but also brings certain dangers to the battery. The fact that the porous cellulose powder filled with lithium ions directly added in Example 3 has a conductivity much lower than that in Example 1 also proves this point. In order to further improve the ionic conductivity of the prepared solid electrolyte, the present invention performs high-temperature carbonization treatment on the prepared lithium ion-filled porous cellulose powder to obtain a porous activated carbon powder containing a large amount of lithium ions, which can effectively form a stable lithium ion transmission channel in the solid polymer electrolyte, greatly improving the electron transmission efficiency of the prepared solid electrolyte.
[0091] By comparing Example 1 and Example 2, it can also be found that in Example 2, the coconut shell fiber is not subjected to a porous treatment, and the obtained activated carbon powder loaded with lithium ions has an ion conductivity lower than that of Example 1 after acting on the solid polymer electrolyte, which indicates that the porous treatment is beneficial to improving the performance of the porous activated carbon powder filled with lithium ions. The present invention believes that this is because the porous treatment can first increase the adsorption rate of coconut shell fiber to lithium ions, and secondly, the porous fiber helps to improve the charge transmission capacity after carbonization, thereby improving the lithium ion transmission performance of the solid polymer electrolyte.
[0092] From Comparative Examples 1, 2, 3 and 4, it can be found that direct carbonization of coconut shell fiber without loading lithium ions has little effect on the improvement of the ionic conductivity of the solid polymer electrolyte, which indicates that lithium ions play a major conductive role in it.
[0093] Test Example 2
[0094] Assembly of solid-state battery: A positive electrode sheet is attached to one side of the cut electrolyte original sheet (20 μm in diameter), and a lithium sheet of equal area (360 μm in thickness) is attached to the other side. After packaging, a solid-state lithium metal battery is obtained. Among them, the positive electrode current collector is carbon-coated aluminum foil, and the negative electrode current collector is copper foil.
[0095] At 1mA / cm 2 At a current density of , the battery is first charged to the cut-off voltage (1V) and then discharged for 1h until the cycle ends, with a cycle number of 200 times.
[0096] Table 2: Cyclic performance test results
[0097] Capacitance drop rate % Example 1 0.67 Example 2 1.03 Example 3 7.36
[0098] As can be seen from Table 2, Example 3 directly uses porous cellulose powder filled with lithium ions, and the stability of its solid electrolyte is significantly reduced compared with Example 1 and Example 2. The present invention believes that this is due to the strong water absorption of cellulose, and the water molecules in cellulose are not conducive to the stability of the solid polymer electrolyte.
Claims
1. A method for preparing a solid polymer electrolyte for a lithium battery, characterized in that: The method comprises the following steps: mixing ceramic electrolyte nanoparticles and porous activated carbon powder filled with lithium ions and uniformly dispersing them in polyethylene oxide to obtain the solid polymer electrolyte for lithium batteries.
2. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 1, characterized in that: The preparation method of ceramic electrolyte nanoparticles comprises the following steps: dissolving lithium nitrate, tetrabutyl titanate, zirconium oxychloride octahydrate and aluminum trichloride hexahydrate in a citric acid-ethylene glycol solution, stirring to form a transparent solution, drying the solution to obtain a transparent gel; and calcining the transparent gel at a high temperature to remove carbon therein to obtain ceramic electrolyte nanoparticles.
3. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 2, characterized in that: Preparation method of ceramic electrolyte nanoparticles, The method comprises the following steps: dissolving 4-5 parts of lithium nitrate, 1-1.5 parts of tetrabutyl titanate, 1.5-2 parts of zirconium oxychloride octahydrate and 3-4 parts of aluminum trichloride hexahydrate in 10-20 parts of citric acid-ethylene glycol solution by mass, stirring to form a transparent solution, drying the solution to obtain a transparent gel; calcining the transparent gel at 600-700° C. for 1-2 hours to remove carbon therein, and obtaining ceramic electrolyte nanoparticles.
4. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 1, characterized in that: The method for preparing porous activated carbon powder filled with lithium ions comprises the following steps: (1) washing, drying, shearing, crushing and sieving coconut shell fiber to obtain coconut shell fiber powder; treating the obtained cellulose with sodium hydroxide aqueous solution, filtering, washing and drying to obtain activated cellulose powder; (2) immersing the activated cellulose powder obtained in step (1) in a copper chloride aqueous solution, stirring, filtering, and oxidizing to obtain a cellulose powder filled with copper oxide; immersing the cellulose powder filled with copper oxide in sulfuric acid, stirring, filtering, washing, and drying to obtain a porous cellulose powder; (3) The porous cellulose powder obtained in step (2), lithium nitrate and water are mixed and stirred, filtered and dried to obtain a porous cellulose powder filled with lithium ions; and the porous cellulose powder filled with lithium ions is calcined in an oxygen-free environment to obtain a porous activated carbon powder filled with lithium ions.
5. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 4, characterized in that: The method for preparing porous activated carbon powder filled with lithium ions comprises the following steps: (1) washing, drying, shearing and crushing coconut shell fiber, passing through a 180-200 mesh sieve to obtain coconut shell fiber powder; treating the obtained cellulose with a 6-8 wt % sodium hydroxide aqueous solution for 1-2 h, filtering, washing and drying to obtain activated cellulose powder; (2) immersing the activated cellulose powder obtained in step (1) in a copper chloride aqueous solution with a concentration of 18-20 wt% at a bath ratio of 1 g: (10-20) mL, stirring for 1-2 h, filtering, and oxidizing at 100-120° C. for 6-8 h to obtain a cellulose powder filled with copper oxide; immersing the above cellulose powder filled with copper oxide in 10-16 wt% sulfuric acid at a bath ratio of 1 g: (10-20) mL, stirring for 15-30 min, filtering, washing, and drying to obtain a porous cellulose powder; (3) Mix 5-10 parts of the porous cellulose powder obtained in step (2), 1.6-2 parts of lithium nitrate, and 40-50 parts of water, and stir for 1-2 hours, filter, and dry to obtain a porous cellulose powder filled with lithium ions; and calcine the porous cellulose powder filled with lithium ions at 600-800° C. in an oxygen-free environment to obtain a porous activated carbon powder filled with lithium ions.
6. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 1, characterized in that: The following steps are involved: Ceramic electrolyte nanoparticles and porous activated carbon powder filled with lithium ions are mixed to obtain a mixed electrolyte; polyethylene oxide is dissolved in anhydrous acetonitrile, and then the mixed electrolyte is added, stirred and repeatedly ultrasonicated to ensure that the mixed electrolyte is fully dispersed, and the obtained uniform suspension is coated on a polytetrafluoroethylene substrate and fully dried under vacuum conditions to obtain a solid polymer electrolyte for lithium batteries.
7. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 6, characterized in that: The method comprises the following steps: mixing ceramic electrolyte nanoparticles and porous activated carbon powder filled with lithium ions in a mass ratio of 1:(0.1-0.2) to obtain a mixed electrolyte; dissolving 8-12 parts of polyethylene oxide in 90-100 parts of anhydrous acetonitrile by mass, then adding 1-1.5 parts of the mixed electrolyte, stirring and ultrasonicating for 40-60 minutes, coating the obtained uniform suspension on a polytetrafluoroethylene substrate, and drying at 50-70°C under vacuum conditions to obtain a solid polymer electrolyte for a lithium battery.
8. A method for preparing a solid polymer electrolyte for a lithium battery as claimed in claim 7, characterized in that: The ultrasonic power is 600-1000W and the frequency is 40-80kHz.
9. A solid polymer electrolyte for lithium battery, characterized in that: The solid polymer electrolyte is prepared by the method for preparing a solid polymer electrolyte for a lithium battery as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing flexible three-dimensional solid electrolyte membrane
CN107887554A
Composite solid electrolyte, all-solid-state lithium ion battery and preparation method thereof
CN113346126A
Preparation method of composite solid electrolyte with soft filler
CN116826159A
Solid electrolyte, composite electrolyte and lithium ion secondary battery including the same
JP2015176857A
Septic tank-integrated modular building structure using architectural foundation and its construction method
KR102821367B1